2014
DOI: 10.1253/circj.cj-66-0082
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Transplantation of Non-Expanded Peripheral Blood-Derived Mononuclear Cells Promotes Improvement of Cardiac Function in Patients With Acute Myocardial Infarction

Abstract: Circulation Journal Official Journal of the Japanese Circulation Society http://www. j-circ.or.jp 1. We would like to rewrite a statement in the Methods and Results section of the Abstract.Original Statement (p.1199, Abstract, Lines 5-10):After successful percutaneous coronary intervention (PCI) for a ST-elevation AMI with occlusion of proximal left anterior descending coronary artery within 24 h, patients were assigned to either a control group or the PBMNC group that received intracoronary infusion of PBMNCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The TOPCARE-AMI Trial in 2004 for AMI patients without a control showed significant improvement in the LVEF, an attenuation of LV dilatation, and reduced infarct size at the one-year follow-up [50]. Tatsumi et al performed an open-label, nonrandomized, controlled clinical trial for AMI patients treated with CPC implantation without using G-CSF and cell expansion, and revealed a significant increase in the LVEF and regional systolic performance at 6 months without any adverse clinical events [61]. The first randomized, double blind, and placebo-controlled study on CPC transplantation demonstrated an improvement in coronary flow reserve, decline in the number of hibernating segments, and an increase in LVEF at 3 months after transplantation, indicating that CPC transplantation was effective for OMI patients [62].…”
Section: Other Clinical Studies In Cellular Cardiomyoplastymentioning
confidence: 99%
“…The TOPCARE-AMI Trial in 2004 for AMI patients without a control showed significant improvement in the LVEF, an attenuation of LV dilatation, and reduced infarct size at the one-year follow-up [50]. Tatsumi et al performed an open-label, nonrandomized, controlled clinical trial for AMI patients treated with CPC implantation without using G-CSF and cell expansion, and revealed a significant increase in the LVEF and regional systolic performance at 6 months without any adverse clinical events [61]. The first randomized, double blind, and placebo-controlled study on CPC transplantation demonstrated an improvement in coronary flow reserve, decline in the number of hibernating segments, and an increase in LVEF at 3 months after transplantation, indicating that CPC transplantation was effective for OMI patients [62].…”
Section: Other Clinical Studies In Cellular Cardiomyoplastymentioning
confidence: 99%
“…Particularly, BM-derived endothelial progenitor cells (EPCs) have been studied by many research groups and have shown therapeutic potentials in animal models of myocardial and peripheral vascular ischaemia (Kalka et al, 2000;Murohara et al, 2000;Schatteman et al, 2000;Kawamoto et al, 2001;Kocher et al, 2001;Iwasaki et al, 2006;Jeong et al, 2009). Moreover, a series of clinical trials using EPCs or similar BM cells has shown therapeutic benefits to treat postmyocardial infarction (MI) cardiac dysfunction and critical limb ischaemia (Assmus et al, 2002;Bartunek et al, 2005;Boyle et al, 2006;Schaefer et al, 2006;Li et al, 2007;Losordo et al, 2007;Stamm et al, 2007;Tatsumi et al, 2007;Hare et al, 2009;Burt et al, 2010;Kuroda et al, 2011;Miettinen et al, 2010). On the other hand, other studies have revealed conflicting results with regard to the effects of BM-derived mononuclear cells (MNCs) on myocardial ischaemia in a similar subset of patients (Janssens et al, 2006;Lunde et al, 2006;Meyer et al, 2006;Penicka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%